Efficiency Analysis of Excavator Nut Inventory Using Economic Order Quantity Method at PT. ABCDE Bekasi-Jawa Barat - Kurniawan, Mohammad Fahmi; Madelan, Sugiyono; Badawi Saluy, Ahmad (Dinasti Publisher, 2021)
Inventory management is one of the keys to the success of the production process in any company, including manufacturing companies. Therefore, determining the optimal amount of inventory is crucial for inventory management. In a production process, sometimes a condition is found where the amount of inventory far exceeds what is needed, so that in the process of implementing the specifications change of an inventory will take quite a long time, this is due to an effort to use up obsolete inventory first, so it is necessary to calculate the optimal value of the company inventory. In this research, using the Economic Order Quantity and Reorder Point analysis method in the POM-QM software, it is expected to determine the optimal value of the purchase amount, Safety Stock, Reorder Point, and the required inventory costs of J950010 nuts. The results showed that although there were differences between the results of the POM-QM calculation and the application in the field, the management of J950010 nut stock is optimal.